Εφαρμογή της μεθόδου παρεμπόδισης της σύζευξης για τον έλεγχο της Ευδεμίδας και διερεύνηση της παρουσίας ωφέλιμων εντόμων ως υποστηρικτική υπηρεσία οικοσυστήματος - Θεοδώρου, Μαρία (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This research was conducted under the AgroLIFE project, a three-year project (02/06/14 - 01/06/17) co-funded by the European Union's LIFE + Nature & Biodiversity. The first part of the survey dealt with the treatment of the insect Lobesia botrana in vineyards of the Commandaria area, which is consider to be the most important enemy of vines. This particular insect causes significant damage to grape flowers, and even more important loss to the unripe and mature berries, depending on their generation of the insect. The aim of the research was to investigate whether the Mating Disruption Technique by using pheromone vaporizers is effective in order to reduce the infection and loss of production both qualitatively and quantitatively. At the same time, there was an investigation into the presence of beneficial insects, which act as a supportive ecosystem service. Beneficial insects are those that can help in dealing with important enemies to the producers. In particular, the main purpose was to investigate whether the presence of raptors and insect pests is affected in three different categories of vineyards, depending on how they are managed.
Keywords: Lobesia botrana; Mating disruption technique; Beneficial insects; Supportive ecosystem service; Lobesia botrana; Μέθοδος παρεμπόδισης της σύζευξης; Ωφέλιμα έντομα; Υποστηρικτική υπηρεσία οικοσυστήματος